ROAD TRAFFIC SAFETY AND ITS IMPACT ON THE DEVELOPMENT OF MODERN ROAD-TRANSPORT EXPERTISE - Mizrabov Ulug’bek Boliqul o’g’li (Journals Park Publishing, 2022)
An increase in the number of vehicles, as well as an increase in speed and intensity of traffic, makes the problem of road safety more urgent. The main indicator of good wheel contact with the road surface is the contact coefficient, which affects the stability and control of the car. The article examines the conditions and conditions that affect the value of the coefficient of adhesion of tires to the road surface. Studies were conducted for various vehicles with and without anti-lock braking system (ABS), as well as for summer and winter tires in dry and wet asphalt and concrete pavement conditions.
Keywords: car, deceleration, adhesion coefficient, road surface, road tests, pneumatic tire